Do Estado União de Jeovah à União dos Posseiros de Cotaxé: transição de movimento sociorreligioso a movimento político e organizado singularidades: transição e longevidade - Garcia, Elio Ramires (2015)
This paper aims to study the transition process taken place in the peasant movement of socio-religious matrix the longest in the history of Brazil, which took place in Cotaxé district in the city of Ecoporanga in the state of Espirito Santo. Will study the locus of this historical fact, its physical and demographic characteristics and the process of occupation of the region, particularly in the period between the years 1930 and 1960.Initially from socio-religious nature, over here termed Cotaxé Movement has its beginnings in the final years of the 1940s, when Udelino Alves de Matos, a well preacher speaker, brings to the region. Allying the speech of the earth with a inaccurate religious background speech, the Bahian preacher proposes the construction of a new federative entity, the Union State of Jeovah at the litigated zone by the states of Espírito Santo and Minas Gerais. Like practical steps, the Bahian preacher organizes an armed group to expel owners and take the initiative of launching the organizational bases of the new State. Settled Union Jeovah by the Military Police of the Espirito Santo, Udelino disappears, or was "disappeared". However, even disappeared Udelino, remains unresolved, especially the issue of ownership and titling of land, the main social actors remain present, both squatters as land grabbers, important individual actors and also institutional violence and the informal violence. In this context of overcoming traumatic, but also of continuities, register the later presence of PCB, operating in the region and mediating the initially socio-religious movement transition to highly political and organized movement, and articulated to other sectors of social movements. This transition, mediated by the Communist Party, constitutes the central problem to be elucidated in this study. The Cotaxé Movement has its end with the exit of the last of the leaders of the squatters during october of 1966, having existed for long 18 years. To achieve the objectives proposed in this study, we used both methodologies and document analysis as in the field of oral history, interviews with a few characters, who experienced, at least in part, those episodes